Factors that hinder the utilisation of intermediary social work support service to alleged child offenders in Mopani District, Limpopo Province - Makwala, Kelebogile Precious (My University, 2022)
The study concentrated on factors that hinder the utilisation of intermediary social work support services to alleged child offenders in Mopani District. The study aimed to assess knowledge from probation officers in respect of awareness, utilisation and effectiveness of referral to intermediary services, as well as the level at which they can refer alleged child offenders to an intermediary. The study employed the qualitative research design. The Integrated Service model was employed to understand the utilisation of intermediary social work support services to alleged child offenders. Purposive sampling was used to obtain nine participants who were probation officers. Ethical clearance was obtained from the University of Limpopo and gatekeepers approval from the Department of Social Development. Participation was voluntary and no one was forced to participate. The findings of the study revealed that there are no clear guidelines or legislation for probation officers to guide them on how and when to recommend the alleged child offenders to the intermediary services. The study also revealed that section 158(2) of the Criminal Procedure Act 51 of 1977 is not effective to alleged child offenders but rather is used to child victims. Therefore, probation officers must have understanding of the role of an intermediary, process and referral when conducting assessments. As a result, the study recommends that the probation officers should come to the developmental level of the child, speak the language of the child and follow up assessment interviews as opposed to informed allegation interviews. However, training is also recommended to all probation officers about the Criminal Procedure Act 51 of 1977 and amendments of the Child Justice Act 75 of 2008 with the inclusion of intermediary services to alleged child offenders
Thesis (M.A. (Social Work)) -- University Of Lmpopo, 2022
Keywords: Mopani District; Intermediary social work support services; Child offenders; Probation officers; Child molestors; Social work with children -- South Africa -- Limpopo; Social service -- South Africa -- Limpopo; Child care services; Probation officers